Innentitelbild: Porous and Water Stable 2D Hybrid Metal Halide with Broad Light Emission and Selective H2O Vapor Sorption (Angew. Chem. 12/2023). (9th February 2023) - Azmy, Ali; Li, Shunran; Angeli, Giasemi K.; Welton, Claire; Raval, Parth; Li, Min; Zibouche, Nourdine; Wojtas, Lukasz; Reddy, G. N. Manjunatha; Guo, Peijun; Trikalitis, Pantelis N.; Spanopoulos, Ioannis
Abstract : Porous and water‐stable hybrid semiconductors as multifunctional materials display traits that are essential for demanding commercial applications. In their Research Article (e202218429), Ioannis Spanopoulos and co‐workers report a strategy for generating porosity in hybrid metal halide semiconductors by using molecular cages as both structure‐directing agents and counter‐cations. This strategy gave rise to a direct bandgap semiconductor with record water stability and selective vapor sorption.